STUDY OF POTASSIUM RELEASE AND ITS RELATIONSHIP WITH CHEMICAL SOIL PROPERTIES AND ITS EFFECT IN ALFAALFA GROWTH IN SOME OF SOILS SALTY IN WASIT PROVINCE - Mahdi Wasmey Seheib; Asmaa Hussein Allawe (Web of Journals Publishing, 2025)
This study was aimed to determine of the chemical and, physical soil properties by potassium release, ten different locations were chose in Waist Province, then chose three locations according to the contrast in its salty and clay contents. These locations are Al-swaira, Nuamaniya and Al-Hay. Potassium was extracted from the studies by different methods such as the chemical methods and the biological methods. These chemical extractions are water, the organic acid solution [(COOH)2, C6H8O7] and Ca-resin. Potassium is extracted by mentioned solutions above (0.5 molar conc) Potassium is extracted by missible displacement. Every technique is about ten periods. The duration of every one is twenty minutes. The total period is about (200) minutes except the resin which is used by Batch equilibrum technique. This technique is about ten periods. The duration of every one is about 7 days. The total period is about (70) days. In this experiment, Alfalfa plant (local classes) was in planted in plastic pots. The volume of every pot is about 3.5 kg ,then cut five often on different time period when reach the flowers percentage (10%) for total growth period (200) days. Potassium is determined in all the extractions and for all the used methods in this study by flame photometer system. The results of this study display that the best extract to release potassium in calcic Iraqi soils is Ca-resin by Batch equilibirum technique in field capacity compared with the organic extracts acidity.